A regularized damage‐plasticity model: micromorphic formulation and numerical aspects. Issue 1 (October 2016) - Brepols, Tim; Wulfinghoff, Stephan; Reese, Stefanie
Abstract: A gradient‐extended damage‐plasticity model is discussed which is based on a micromorphic approach according to Forest [1]. Damage and plasticity are treated as independent but strongly coupled dissipative phenomena by considering separate yield and damage loading functions to describe the onset of plastic flow and / or damage evolution. A numerical benchmark test conducted in the study reveals that the model is able to essentially cure the well‐known mesh‐dependence issue which is known from finite element simulations involving conventional (i. e. 'local') damage material models. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)